Peran kepemilikan institusional, perencanaan pajak dan dewan komisaris asing terhadap nilai perusahaan - Rahma, Anita Ade; Nabawi, Lisa; Wijaya, Ronni Andri (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2019)
The purpose of this study is to analyze the role of institutional leadership, tax planning and foreign board of commissioners on firm value. The population in this study were 615 companies listed on the Indonesia Stock Exchange in 2015-2017. The sample was chosen using purposive sampling to get a total sample of 325 companies with a total of 975 observations of company data. The results of this study indicate that institutional leadership and tax planning have no role in increasing company value. While the foreign board of commissioners showed a significant influence on the value of the company. This proves that there is a need for diversity in the structure of the board that can trigger an increase in the value of the company. In addition, the presence of a foreign board is needed for the progress of the companyKeywords: Investment decisions; funding decisions; dividend policy; company value